Antibodies to contactin‐1 in chronic inflammatory demyelinating polyneuropathy. Issue 3 (31st December 2012) - Querol, Luis; Nogales‐Gadea, Gisela; Rojas‐Garcia, Ricard; Martinez‐Hernandez, Eugenia; Diaz‐Manera, Jordi; Suárez‐Calvet, Xavier; Navas, Miquel; Araque, Josefa; Gallardo, Eduard; Isabel Illa,
<x xml:space="preserve">Abstract</x> Objective Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a frequent autoimmune neuropathy with a heterogeneous clinical spectrum. Clinical and experimental evidence suggests that autoantibodies may be involved in its pathogenesis, but the target antigens are unknown. Axoglial junction proteins have been proposed as candidate antigens. We examined the reactivity of CIDP patients' sera against neuronal antigens and used immunoprecipitation for antigen unraveling. Methods Primary cultures of hippocampal neurons were used to select patients' sera that showed robust reactivity with the cell surface of neurons. The identity of the antigens was established by immunoprecipitation and mass spectrometry, and subsequently confirmed with cell‐based assays, immunohistochemistry with teased rat sciatic nerve, and immunoabsorption experiments. Results Four of 46 sera from patients with CIDP reacted strongly against hippocampal neurons (8.6%) and paranodal structures on peripheral nerve. Two patients' sera precipitated contactin‐1 (CNTN1), and 1 precipitated both CNTN1 and contactin‐associated protein 1 (CASPR1). Reactivity against CNTN1 was confirmed in 2 cases, whereas the third reacted only when CNTN1 and CASPR1 were cotransfected. No other CIDP patient or any of the 104 controls with other neurological diseases tested positive. All 3 patients shared common clinical features, including advanced age, predominantly motor involvement, aggressive symptom onset, early axonal involvement, and poor response to intravenous immunoglobulin. Interpretation Antibodies against the CNTN1/CASPR1 complex occur in a subset of patients with CIDP who share common clinical features. The finding of this biomarker may help to explain the symptoms of these patients and the heterogeneous response to therapy in CIDP. ANN NEUROL 2013;73:370–380